Потенційні характеристики ректен - Алєксєєв, В. О. (ХНУРЕ, 2025)
An assessment of the potential characteristics of rectennas with a half-wave rectification circuit has been conducted. The key factors affecting the efficiency of rectennas have been identified, including the type of rectifying elements, frequency characteristics, parasitic losses, and temperature fluctuations. Practical recommendations are provided for selecting rectifying elements and optimizing rectification circuits to achieve maximum energy conversion efficiency under conditions of limited power consumption.
Keywords: ректена; rectennas